Psychological And Didactic Approaches to Studying the Category of Conditional Relations in Modern Russian Language by Students of Secondary Special Educational Institutions - Jamolova Shakhlo Shavkatovna (Zien Journals, 2021)
All words of the English language are divided into certain lexical and grammatical categories, called parts of speech. Parts of speech are the main lexicographic categories into which words of a language are distributed based on the following characteristics: a) semantic (generalized meaning of an object, action or state, quality), b) morphological (morphological categories of a word), and c syntactic (syntactic functions of a word)
Keywords: English language; lexical and grammatical categories; lexicographic; syntactic